2020
DOI: 10.1177/2192568220913006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Therapy-Oriented Classification of Intervertebral Vacuum Phenomenon With Evaluation of Intra- and Interobserver Reliabilities

Abstract: Study Design: Diagnostic study, level of evidence III. Objectives: Low back pain is a common cause of disability among elderly patients. Percutaneous discoplasty has been developed as a tool to treat degenerative disease when conservative management is not successful. Indications for this procedure include low back pain and the presence of vacuum phenomenon. The objective of this study was to describe a new classification of vacuum phenomenon based on computed tomography scan in order to improve the indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…The importance of this parameter is unclear in the clinical practice. A recent study investigating the Vacuum Phenomenon (VP) impact for PCD indication concluded that the volume of vacuum could not be used as a proper indication for this surgery [36]. Moreover, during the PCD procedure, the patient position aims at enlarging the intervertebral space by reducing the segmental lordosis.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this parameter is unclear in the clinical practice. A recent study investigating the Vacuum Phenomenon (VP) impact for PCD indication concluded that the volume of vacuum could not be used as a proper indication for this surgery [36]. Moreover, during the PCD procedure, the patient position aims at enlarging the intervertebral space by reducing the segmental lordosis.…”
Section: Discussionmentioning
confidence: 99%
“…The articles found included four prospective studies ( 9 , 16 18 ), one case study ( 19 ), two diagnostic studies ( 20 , 21 ), five retrospective studies ( 22 26 ), four biomechanical studies whose only three published ( 27 29 ). The four remaining publications were correspondence to the Editor articulated around two distinct conversations.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers presented case studies ( 9 , 19 ). Camino-Willhuber et al focused on the development of a methodology to fine-tune the diagnosis of cases requiring PCD as a treatment ( 20 ). Eltes et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accordion phenomenon is defined as the difference in the disc space observed on x-ray or computed tomography (CT) images taken in both standing and supine positions, which results in a discrepancy of local spinal alignment. Moreover, this phenomenon occurs in advanced degeneration of the intervertebral disc with vacuum phenomenon and is considered to cause mechanical low back pain 2,3 .…”
mentioning
confidence: 99%